DevOps theory to practice. (Pragmatic AI Solutions, 2022)
DevOps Theory to Practice Go from theory to implementation in this DevOps course with Python and AWS This video course will show you how to start your first day as a DevOps Engineer and progress. Topics Covered Include: DevOps Theory Learn useful Python skills for DevOps including working with the filesystem and processes. Build an AWS Boto3 tool with Python Fire for translation and test it with CI/CD. Build a containerized FastAPI service deployed to AWS App Runner through continuous delivery. Learning Objectives Learn the theory behind DevOps Walk through the implementation of several O'Reilly books including Python for DevOps, AWS for C# and Enterprise MLOps. Build an AWS Translation Service tool with Python and Boto3 Deploy a Pandas FastAPI web service with Python and FastAPI and AWS App Runner Build and use AWS CodeBuild with AWS App Runner Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.